1983
DOI: 10.1084/jem.158.5.1547
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a clonally restricted 90 kD heterodimer on two human cloned natural killer cell lines. Its role in cytotoxic effector function.

Abstract: The present studies were carried out to identify surface molecules involved in the cytotoxic effector function of a human natural killer (NK) clone termed JT9. This clone represents a mature T lymphocyte (T3+T8+T11+) mediating NK-like activity. Using JT9 for immunization, one monoclonal antibody termed anti-NKTa was selected that blocked the cytotoxicity of the clone towards K562 cells. Reactivity of anti-NKTa antibody was assessed using a large panel of lymphoid and nonlymphoid cells including a variety of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
2

Year Published

1985
1985
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 23 publications
2
36
2
Order By: Relevance
“…The results with these cells, however, are in marked contrast to those obtained in previous studies in the mouse (16) and human (17), which have suggested that a T cell receptor-like molecule is present in IL-2-propagated cloned cells with NK-like activity. Several possible reasons for this difference are: (a) differences between in vitro grown clones derived from normal ceils and in vivo derived tumors, (b) differences between species, or, most likely, (c) differences in the origin of the cytotoxic cells.…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…The results with these cells, however, are in marked contrast to those obtained in previous studies in the mouse (16) and human (17), which have suggested that a T cell receptor-like molecule is present in IL-2-propagated cloned cells with NK-like activity. Several possible reasons for this difference are: (a) differences between in vitro grown clones derived from normal ceils and in vivo derived tumors, (b) differences between species, or, most likely, (c) differences in the origin of the cytotoxic cells.…”
contrasting
confidence: 56%
“…Several possible reasons for this difference are: (a) differences between in vitro grown clones derived from normal ceils and in vivo derived tumors, (b) differences between species, or, most likely, (c) differences in the origin of the cytotoxic cells. Since these previous studies (16,17) examined cytotoxic lines with T celllike as well as NK-like characteristics, it is quite possible that these lines were derived from T cells rather than LGL. Several groups (16,17) have reported that clones of cytotoxic T lymphocytes (CTL) can, under appropriate conditions, develop NK-like activity, either together with CTL activity or after the loss of specific reactivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The activated PBMC were then washed four times to remove the mitogens, and were resuspended in RPMI 1640 supplemented with 2.5% human AB serum. After 40 h of incubation at 37°C, the cells were pelleted at 500 g, and the LCM was sterilized by passage through 0.45 #m filters and stored at -70°C until it was used for cloning or subcloning the JTB18 cells (21)(22)(23)(24). All NK cells used in these studies were subcloned at least four times at 100 cells/well on a feeder layer of allogeneic irradiated PBMC plus irradiated EBV-transformed B cells.…”
Section: Methodsmentioning
confidence: 99%
“…Cytotoxicity assays with human tumor lines used as targets were performed according to a standard chromium-release method (21)(22)(23)(24). The K562 cell line was established from a patient with chronic myeiogenous leukemia and the KG1 cell line from a patient with acute myeloblastic leukemia.…”
Section: Radiolabeling Of Nk-cloned Cells and Characterization Of Celmentioning
confidence: 99%